PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN DAN PROFITABILITAS SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - NI LUH LAKSMI RAHMANTARI (GANEC SWARA, 2021)
This study aims to (1) analyze the effect of Corporate Social Responsibility on firm value, (2) analyze company size on firm value, (3) analyze profitability on firm value, (4) analyze company size in moderating the relationship between Corporate Social Responsibility towards Firm value (5) analyzes profitability in moderating the relationship between Corporate Social Responsibility and firm value. Firm value is influenced by Corporate Social Responsibility, company size, and profitability. This study uses Analysis Moderated Regression with SPSS for Windows 25.0. The sample in this study used eight pharmaceutical companies listed on the Indonesia Stock Exchange. Using the annual report (annual report) with a span of 2014-2017. The results of the research obtained are (1) Corporate Social Responsibility has a significant positive effect on firm value, (2) Firm size has a significant positive effect on firm value, (3) Profitability has a significant negative effect on firm value, (4) Firm size is unable to moderate the relationship. between Corporate Social Responsibility (CSR) and company value, (5) Profitability is not able to moderate the relationship between Corporate Social Responsibility (CSR) and firm value. The findings of this study are expected to be able to provide an understanding that companies are more open to social and environmental responsibility information with more updated measurements and are based on GRI 4. Then companies need to also look at technical fundamentals, meaning that they look more at the long-term side and not only the short-term side in increasing company value